2019
DOI: 10.1187/cbe.17-07-0137
|View full text |Cite
|
Sign up to set email alerts
|

Retention following Two-Stage Collaborative Exams Depends on Timing and Student Performance

Abstract: Multistage collaborative exams are implemented to enhance learning and retention of course material. However, the effects of multistage collaborative exams on retention of course content are varied. These discrepancies may be due to a number of factors. To date, studies examining collaborative exams and content retention have used questions that all, or mostly, require students to select an answer, rather than generate one of their own. However, content retention can improve when students generate their own re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In some cases, practice quizzing even enhances learners’ ability to transfer learning to new contexts, such as when solving application questions (for a review, see Pan and Rickard, 2018). Moreover, quizzing benefits have been observed for educationally relevant materials and in classroom settings (e.g., McDaniel et al , 2007), including in biology courses (e.g., Bailey et al , 2017; Carpenter et al , 2017; Pape-Lindstrom et al , 2018; Cooke et al , 2019; Walck-Shannon et al , 2019), and with formats ranging from free recall (e.g., McDaniel et al , 2009) to cued recall (e.g., Pan et al , 2015) and multiple-choice tests (e.g., Little et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, practice quizzing even enhances learners’ ability to transfer learning to new contexts, such as when solving application questions (for a review, see Pan and Rickard, 2018). Moreover, quizzing benefits have been observed for educationally relevant materials and in classroom settings (e.g., McDaniel et al , 2007), including in biology courses (e.g., Bailey et al , 2017; Carpenter et al , 2017; Pape-Lindstrom et al , 2018; Cooke et al , 2019; Walck-Shannon et al , 2019), and with formats ranging from free recall (e.g., McDaniel et al , 2009) to cued recall (e.g., Pan et al , 2015) and multiple-choice tests (e.g., Little et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Effect on improved learning: Cooke, Weir, and Clarkston (2019) made the point that comparing two-stage examination studies on whether they improve retention of material covered is difficult, as studies vary widely in their subject matter, implementation, and time span over which retention is tested. The studies included in this narrative review found benefits of two-stage examinations varied between the short and long term (Cooke et al, 2019;Vogler & Robinson, 2016) or between different cohorts of students (Cao & Porter, 2017) or between questions of different difficulty levels (Deng & Luo, 2018). Further studies in a variety of settings will be helpful in further elucidating the effects of two-stage examinations on learning.…”
Section: Student Responsementioning
confidence: 99%
“…Instructors can also consider implementing alternate means of assessment, such as two-stage exams that allow group collaboration in the second part. Such two-stage exams have been shown to promote deeper learning and increased retention in biology classes ( 59 , 60 ). While there has been no work that I am aware of that examines the influence of two-stage exams on student cheating, it is possible that students will cheat less on such assessments, knowing they will be granted the chance to collaborate with their peers.…”
Section: What Strategies Can Biology Instructors Take To Uphold Academentioning
confidence: 99%